2017
DOI: 10.1177/1039856217695870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of yoga as an adjuvant treatment for combat-related posttraumatic stress disorder

Abstract: A range of benefits were observed after yoga, consistent with the theoretical construct for the long history of yoga as a strategy to reduce stress and promote well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The seven single-group studies were not included in the metaanalysis; six of these studies resulted in a significant decrease in overall PTSD symptomatology (Collinge et al, 2012;Gordon et al, 2016;McCarthy et al, 2017;Price et al, 2017;Staples et al, 2013;Walker & Pacik, 2017), and the seventh study only showed a significant decrease in hyperarousal symptoms (Staples et al, 2013). For the 15 studies included in the metaanalysis, a random effects model effect size was calculated for all analyses because of the large heterogeneity in the interventions across the included studies (see Table S1).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seven single-group studies were not included in the metaanalysis; six of these studies resulted in a significant decrease in overall PTSD symptomatology (Collinge et al, 2012;Gordon et al, 2016;McCarthy et al, 2017;Price et al, 2017;Staples et al, 2013;Walker & Pacik, 2017), and the seventh study only showed a significant decrease in hyperarousal symptoms (Staples et al, 2013). For the 15 studies included in the metaanalysis, a random effects model effect size was calculated for all analyses because of the large heterogeneity in the interventions across the included studies (see Table S1).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
“…The selected studies included both civilian participants and veterans as well as both men and women. A total of 11 studies involved a form of yoga (Carter et al, 2013;Descilo et al, 2009;Jindani, Turner, & Khalsa, 2015;McCarthy et al, 2017;Mitchell et al, 2014;Price et al, 2017;Seppälä et al, 2014;Staples, Hamilton, & Uddo, 2013;Thordardottir, Gudmundsdottir, Zoega, Valdimarsdottir, & Gudmundsdottir, 2014;Van der Kolk et al, 2014;Walker & Pacik, 2017), whereas the other studies involved a variety of other BMOIs. The control conditions were waitlist (Carter et al, Rosenbaum, Sherrington, & Tiedemann, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that a 3‐week daily intensive treatment program (ITP) that delivered cognitive processing therapy (CPT), mindfulness, yoga, and other services led to large reductions in PTSD and depression symptoms among veterans with PTSD (Zalta et al., 2018). There is some evidence to suggest that integrative treatments, such as mindfulness and yoga, which are frequently offered in ITPs (Harvey et al., 2017), may lead to sleep improvements among veterans (McCarthy et al., 2017; Nakamura, Lipschitz, Landward, Kuhn, & West, 2011; Staples, Hamilton, & Uddo, 2013). Thus, we sought to examine (a) the degree to which self‐reported insomnia symptoms improved over the course of the ITP, (b) whether baseline insomnia symptoms predicted changes in PTSD and depression severity, and (c) whether changes in self‐reported insomnia symptoms predicted changes in PTSD and depression severity.…”
mentioning
confidence: 99%
“…The benefits of yoga have been demonstrated among non-veteran 13,14 and veteran populations 15,16 with chronic low back pain, and promising results have been found for other conditions experienced by military personnel and veterans, including combat stress 17 and PTSD. 18,19 Other recent studies of yoga for PTSD remain quite small, 20,21 but many researchers await the results of a full-scale VA-funded randomized controlled trial, which are expected in 2018. 22 However, further study of yoga as a treatment option for veterans and military personnel with mental health and chronic pain disorders is needed.…”
Section: Introductionmentioning
confidence: 99%